Penggunaan Kata Slang Bahasa Mandarin Pada Film “Let The Bullets Fly” dan “Caught In The Web” - Zuo Ling Jiao; Michellin Stevanny (Journal of Language, Literature and Teaching, 2019)
Slang words are the social variation which has distinctive characteristic and confidential in nature. It means that the variation is used for certain community. Slangs are divided into proper slang, taboo slang, vogue slang, proxy slang and pragmatic slang. This research was intended to describe slangs in Let the Bullets Fly and Caught in the Web. The theory used in this research was the theory of slang words. The data collected in this research was documentation technique; and the source of the data was the dialogue in Let the Bullets Fly and Caught in the Web. The result showed that there were 4 types of slangs found in both of the movies, they were: proper slang, taboo slang, vogue slang, and proxy slang. Taboo slang was dominantly used in both of the movies. The reasons for using these slangs were to show jokes, to show the aesthetic of the language, to avoid cliché, to enrich vocabulary, and to add emotional appeal in Let the Bullets Fly dan Caught in the Web movie.